2021
DOI: 10.3390/electronics10111314
|View full text |Cite
|
Sign up to set email alerts
|

Data Integrity Preservation Schemes in Smart Healthcare Systems That Use Fog Computing Distribution

Abstract: The volume of data generated worldwide is rapidly growing. Cloud computing, fog computing, and the Internet of Things (IoT) technologies have been adapted to compute and process this high data volume. In coming years information technology will enable extensive developments in the field of healthcare and offer health care providers and patients broadened opportunities to enhance their healthcare experiences and services owing to heightened availability and enriched services through real-time data exchange. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Alam et al [24] suggested Edge-of-Things Computation (EoTC) to reduce healthcare data processing costs. In addition, a distributed provisioning technique based on the Alternating Direction Method of Multipliers (ADMM) is described, along with a portfolio optimization strategy for choosing virtual machines (VMs) to handle healthcare data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Alam et al [24] suggested Edge-of-Things Computation (EoTC) to reduce healthcare data processing costs. In addition, a distributed provisioning technique based on the Alternating Direction Method of Multipliers (ADMM) is described, along with a portfolio optimization strategy for choosing virtual machines (VMs) to handle healthcare data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A physician treats more than 80% of patients with symptoms for which no diagnosis has been made. Only 10% of people seek help from a mental health expert [5,6]. Patients are not receiving the treatment they require, as 70% of people with depression go untreated.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a fog computing paradigm is susceptible to different threats, such as malicious attacks and technical issues. In this context, the end-users' data traveling through fog computing nodes to the cloud is vulnerable to different violations, such as data integrity violation [13]. Therefore, it is necessary to design an approach to protect end-users' data confidentiality, availability, and integrity by ousting the rogue fog nodes.…”
Section: Introductionmentioning
confidence: 99%